The Frayer Model Effectiveness in The Arabic Vocabulary Development for Students in Madrasah - Maswani; N. Lalah Alawiyah; Safira (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study aims to improve the vocabulary mastery of grade XI students of Madrasah Aliyah Negeri (MAN) 11 Jakarta through the Frayer model learning strategy. This type of research is classroom action research, which has four components proposed by Kurt Lewin: planning, action, observation, and reflection. Data collection techniques are done through tests (pretest and posttest), direct observation, interviews, and documentation with data sources from learners, Arabic teachers, and collaborators. In contrast, the data processing method includes data selection and classification, presentation, data processing, and conclusion. Based on learning outcomes, the recapitulation of the average score of students in the first cycle was 70,68 (40% who achieved the Minimum Completeness Criteria). Therefore, researchers continue the second cycle. In cycle II, the average score of students was 77 (86% exceeded the Minimum Completeness Criteria). Based on the results of cycle I and II data, it can be concluded that using Frayer model learning strategies effectively increases students' value in learning vocabulary in madrasah. Thus, using the Frayer model in developing Arabic vocabulary for madrasa students has broad implications, including improving vocabulary understanding, developing critical thinking skills, increasing learning independence, and providing diverse learning approaches.